Correction to: Effect of Motivational Interviewing, Dietary Advice, and Physical Activity on Fetal-Neonatal Outcome in Pregnant Women with Metabolic Syndrome: A Randomized Controlled Trial - Farideh Mohsenzadeh-ledari; Zahra Motaghi; Ziba Taghizadeh; Afsaneh Keramat; Ali Najafi; Mahmood Moosazadeh; Shahla Yazdani (Journal of Mazandaran University of Medical Sciences, 2022)
Correction to: Effect of Motivational Interviewing, Dietary Advice, and Physical Activity on Fetal-Neonatal Outcome in Pregnant Women with Metabolic Syndrome: A Randomized Controlled Trial